2012
DOI: 10.1089/lap.2012.0177
|View full text |Cite
|
Sign up to set email alerts
|

Modified Techniques and Early Outcomes of Totally Laparoscopic Total Gastrectomy with Side-to-Side Esophagojejunostomy

Abstract: Our TLTG with side-to-side esophagojejunostomy method can be a feasible and safe option for patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…Steichen introduced a functional end-to-end anastomosis that has been adopted worldwide [16]. Matsui et al and Lee et al concluded that functional end-to-end esophagojejunostomy after a total gastrectomy is convenient, safe, reliable, and independent of the esophagus and depth of the esophageal hiatus [17, 18]. Functional end-to-end esophagojejunostomy after total gastrectomy in open surgery has become accepted, whereas laparoscopic esophagojejunostomy seems quite rare.…”
Section: Discussionmentioning
confidence: 99%
“…Steichen introduced a functional end-to-end anastomosis that has been adopted worldwide [16]. Matsui et al and Lee et al concluded that functional end-to-end esophagojejunostomy after a total gastrectomy is convenient, safe, reliable, and independent of the esophagus and depth of the esophageal hiatus [17, 18]. Functional end-to-end esophagojejunostomy after total gastrectomy in open surgery has become accepted, whereas laparoscopic esophagojejunostomy seems quite rare.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, totally laparoscopic distal gastrectomy is increasingly employed and has a proven history of safety and feasibility[ 2 - 8 ]. However, although scholars have reported a variety of totally laparoscopic total gastrectomy (TLTG) methods[ 3 , 9 - 13 ], this technique has not been widely adopted because of the technological difficulty inherent in digestive reconstruction. Interest in improving the postoperative appearance and quality of life (QoL) in patients with gastric cancer has been increased.…”
Section: Introductionmentioning
confidence: 99%
“…These anastomosis techniques are less technically complex. They can effectively prevent the occurrence of anastomotic stenosis (23)(24)(25)(26). However, the closure of the joint opening with the Endo GIA makes the overlap procedure easier but tends to cause stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…4 ± 9 . 4 ( 2 6 -4 1 ) m i n , intraoperative bleeding was 141.2 ± 24.9 (130-160) mL, and the number of resected lymph nodes was 23 ± 8 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Patients who underwent hand-sewn esophagojejunostomy did not differ significantly from those who underwent conventional mechanical esophagojejunostomy ( Table 2).…”
Section: Surgery Detailsmentioning
confidence: 99%